Pengaruh Liquid Hold-Up terhadap Transisi Pola Aliran 2 Fasa Air-Udara dari Stratified Ke Slug pada Pipa 50 mm - Andinusa Rahmandhika; Ali Saifullah; Pathur Razi Ansyah; Ali Mokhtar (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2020)
The slug flow pattern is one of the most avoiding factors in piping systems due to its destructive characteristics. Research on the criteria of the slug formation is still the concern. The present study focused on finding out the influence of liquid hold-up toward the transition of the flow pattern from stratified to slug pattern. It was conducted on a 50 mm-diameter horizontal acrylic pipe. The visual data was obtained from a fully developed area (180-210 D) by variations of liquid superficial rate (JL) of 0,03-0,3 m/s and gas superficial rate (JG) from 0,7 to 3,77 m/s. The high-speed camera with 2000 fps recording speed was the instrument to obtain the visual data. The measurement of the liquid hold-up is made by Constant Electric Current Method (CECM). The drastic decrement of liquid hold-up value on the wave growth mechanism (JG â‰¤ 1,88 m/s) indicated the changes in flow patterns from the stratified to the slug pattern, while on the wave coalescence mechanism (JG > 1,88 m/s) the liquid hold-up remains increases. The pattern change from pseudo slug to the slug pattern was not decreasing on its film thickness, yet, it tends to increase the frequency and the liquid slug length.